2005
DOI: 10.1021/ic0501622
|View full text |Cite
|
Sign up to set email alerts
|

Heterobimetallic Complexes of Cobalt(IV) Porphyrin−Corrole Dyads. Synthesis, Physicochemical Properties, and X-ray Structural Characterization

Abstract: The synthesis of a novel family of heterobinuclear cofacial biphenylene (B), anthracene (A), 9,9-dimethylxanthene (X), or dibenzofuran (O) bridged porphyrin-corrole complexes, (PCY)MClCoCl, is reported, M being either an iron(III) or manganese(III) ion. Each complex was characterized by electrochemistry, mass spectrometry, UV-vis, IR, and electron spin resonance spectroscopy. Unlike previously examined biscobalt porphyrin-corrole dyads, the cobalt ion of the corrole moiety is present in a high-valence +4 oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…These results are general and may be pertinent to other redox-active macrocycles. Kadish and co-workers have shown that the selective reduction of O 2 to water 54 can be accomplished using Co 2 (III,III) biscorrole Pacman 55 and porphyrin-cor- …”
Section: Discussionmentioning
confidence: 99%
“…These results are general and may be pertinent to other redox-active macrocycles. Kadish and co-workers have shown that the selective reduction of O 2 to water 54 can be accomplished using Co 2 (III,III) biscorrole Pacman 55 and porphyrin-cor- …”
Section: Discussionmentioning
confidence: 99%
“…Since a cooperative redox activity is not required from two cofacial porphyrins, the second site may be redox inactive or completely absent. Kadish et al (135) have shown that similar selectivities for the 4e À reduction of O 2 to H 2 O can be accomplished using dicobalt(III)-biscorrole Pacman (136) and porphyrin-corrole Pacman assemblies (137). Moreover, the 4e À pathway is accessible for porphyrin-corrole Pacman systems in which the porphyrin macrocycle is unmetalated (138).…”
Section: Oxygen Activation Chemistry Of Pacman and Hangmanmentioning
confidence: 98%
“…All subsequent aqueous solutions were prepared with deionized water of resistivity not less than 18 MX cm. The synthesis and characterization of the heterobimetallic porphyrin-corrole complexes (PCY)MClCoCl (Y = A, B, O, X and M = Fe III , Mn III ) used in this study were reported elsewhere [34,35].…”
Section: Chemicals and Compoundsmentioning
confidence: 99%
“…These results suggest that the cobalt porphyrin macrocycle not present in (BCY)Co 2 or (PCY)H 2 Co plays a key role in the initial stage of O 2 reduction. We were therefore interested in examining the catalytic activity for a similar series of recently characterized [34,35] heterobinuclear face-to-face porphyrin-corrole dyads of the form (PCY)MClCoCl (where Y = A, B, X, or O, M = Fe(III) or Mn(III)), C represents a Co(III) corrole and P an Fe(III) or Mn(III) porphyrin linked by a rigid spacer Y (Chart 1). These results are reported in the present paper and provide a clear picture as to the role of the cobalt porphyrin in the electrocatalytic process.…”
Section: Introductionmentioning
confidence: 99%